The Health Educator Changing Times, Changing Needs: The Evolution from Instructor to Facilitator - Jalang'o, Atieno G. (Journal of Social Health and Diabetes, 2019)
The health scene is undergoing numerous transitions worldwide. Among the forefront health issues are the escalating incidence of noncommunicable and chronic diseases. The nature of these conditions imposes a significant burden on health resources. However, the greater and often silent brunt is borne by the people afflicted by them. They are charged with making lifelong, daily decisions that significantly bear an impact on their care. The health educator workforce is dwindling, but the need for health literacy is on the rise. It is therefore critical that health educators need to be trained in a way that ensures their performance in imparting health-related knowledge and skills is maximized to ensure optimal outcomes in persons living with chronic disease. Patient empowerment is key, and embracing the patients as partners in the education process rather than recipients is advocated by numerous authors. It is also important to ensure we embrace evidence that have proven useful in other areas such as HIV/AIDS management. Last, it is useful to embrace the changing role of the health education, not merely as instructor charged to deliver health information but rather as a facilitator of behavior change.
Keywords: global health care scene; health educator; health care information